Nouvelles réminiscences littéraires décelées dans la Vie et les Miracles de saint Thècle (BHG 1717-1718) - Narro, Ángel, 1985- (Analecta Bollandiana: Revue critique d'hagiographie, 2012)
This article presents new literary reminiscences of pagan and Christian texts in the Life and Miracles of Saint Thecla (BHG 1717-1718). The highlighted passages, borrowed from authors such as the historians Thucydides, Polybius and Diodorus Siculus, the rhetoricians Themistius and Libanius or the Christian writers Eusebius and John Chrysostom, prove, as if it were necessary, Gilbert Dagron’s opinion about the erudition of the anonymous author of the text.